Studies Polymorphism of Blood Plasm Protein in Gurami (Osphronemus gouramy Lac) in Jember County - Rike Oktarianti; Mamik Pristiwindari (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
The objective of this research was to study the blood protein polymorphism of gurami (Osphronemus gouramy Lac). Blood sample were collected from 55 gurami. Polyaacrilamide Gel Electrophoresis (PAGE) was used in the blood plasm protein analysis. Identification of protein bands on gel are determinated by comparing the molecul weight of those test group protein with the marker protein. The result showed that the locus albumin, pre-albumin and transferin are polymorphic. Locus albumin, pre-albumin and transferin are controlled by three alleles ie A, B and C. The total heterozygozity of gurami is 52 %.